The Relationship between Critical Thinking Skills of Educational Administrators and Learning Organization under The Secondary Educational Service Area Office Bangkok 2 - Phacharapakornpong, Jitpanu; Lapjaroen, Supawadee (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
The purposes of this research were to 1) study the Critical thinking skills of the school administrators 2) study the Organizational learning in educational institutions and 3) study the relationship between Critical thinking skills of school administrators and the Organizational learning in educational institutions. The results of this research were as follow: the Critical thinking skills of the school administrators was at a high level for all aspects. the Organizational learning in educational institutions was at a high level for all aspects. The relationship between Critical thinking skills of school administrators and the Organizational learning in educational institutions under the office of secondary educational service Bangkok area 2 in relation to overall there is a medium level of positive relationship and statistically significant at .01